Australian Bank and Corporate Sector Vulnerabilities : An International Perspective - Takats, Elod (IMF Working Papers; Working Paper ;, 2009)
This paper focuses on how the exposure to the corporate sector may impact the health of the Australian banking system. It also compares Australian banks with their international peers. Finally, it investigates banks' exposure to credit risk using the new Basel II Pillar 3 disclosure data. The analysis shows that Australian banks have remained very sound by international standards, despite the global financial turmoil. While the international downturn points to several vulnerabilities, the risks from the corporate and household sectors appear to be manageable.